THE INFLUENCE OF THE VOLUME OF MOTORCYCLE ON THE TRAFFIC SPEEDS ON THE OTTO ISKANDARDINATA ROAD IN SAMARINDA CITY - SAHRANI AR, MUHAMMAD (KURVA S JURNAL MAHASISWA, 2020)
Samarinda City currently has a population of around 872,768 people (BPS East Borneo 2019) which is included in the most populous city in East Kalimantan. With the increase in population in Samarinda City will increase the movement and need for access to transportation facilities and infrastructure. The number of vehicles in East Kalimantan, especially motorcycles, increased by 2,228,292 (BPS East Borneo 2015). With the high growth in the number of vehicles, this makes several lanes in the city of Samarinda very risky to experience a decrease in traffic speeds such as on the Otto Iskandardinata Road section. Otto Iskandardinata Road is a road that belongs to the UD 2/2 Collector category with a length of 0.960 km and a width of 8.6 m, data was taken for 2 weeks, from 11 February 2019 - 24 February 2019 with a time of research of 8 hours. The observation points were carried out at 2 observation points. In this study, using a conventional calculation method, namely by calculating the volume of vehicles using MKJI 1997. Based on the results of calculations it can be seen that when the volume of the vehicle is small ie in the morning the vehicle speed when passing is relatively high and when the traffic volume has increased during the afternoon the traffic speed decreases. The solution that can be done to overcome the problems in Jalan Otto Iskandardinata City in Samarinda is to change the type of road that was originally from 2 / 2UD to 4 / 2UD. It can be seen that the degree of saturation has improved, which was originally 0.65 (2 / 2UD) to 0.40 (4/2 UD). So the road with type 4/2 UD shows better ability to accommodate the traffic flow on the Otto Iskandardinata road in Samarinda City.